European Network of Breast Development and Cancer turned 10 years: a growing family of mammary gland researchers - Koledova, Zuzana; Howard, Beatrice A; Englund, Johanna; Bach, Karsten; Bentires-Alj, Mohammed; Gonzalez-Suarez, Eva (Breast cancer research, 2018)
The European Network for Breast Development and Cancer (ENBDC), a worldwide network ( http://www.enbdc.org/ ), celebrated its tenth anniversary with a fantastic meeting last March 15-17, 2018 in Weggis with 76 attendees.
Keywords: Humans; European Network of Breast Development and Cancer Laboratories; Imaging; Female; Breast; Single cell RNAseq; lidé; Research Personnel; Mammary Glands, Human; výzkumní pracovníci; Breast Neoplasms; ženské pohlaví; Myeloid cells and neutrophils; biomedicínský výzkum; nádory prsu; mléčné žlázy lidské; Tumor immunology; Biomedical Research; prsy